Concerted actions of PRR- and NLR-mediated immunity. Issue 5 (30th September 2022) - Rhodes, Jack; Zipfel, Cyril; Jones, Jonathan D.G.; Ngou, Bruno Pok Man
Abstract: Plants utilise cell-surface immune receptors (functioning as pattern recognition receptors, PRRs) and intracellular nucleotide-binding leucine-rich repeat receptors (NLRs) to detect pathogens. Perception of pathogens by these receptors activates immune signalling and resistance to infections. PRR- and NLR-mediated immunity have primarily been considered parallel processes contributing to disease resistance. Recent studies suggest that these two pathways are interdependent and converge at multiple nodes. This review summarises and provides a perspective on these convergent points.